Clinicopathological characteristics and cancer-specific prognosis of primary pulmonary lymphoepithelioma-like carcinoma: a population study of the US SEER database and a Chinese hospital - Zhang, Qun; Dai, Yuan; Jin, Linling; Shi, Shuangshuang; Liu, Chang; Rong, Rong; Sun, Wenkui; Dai, Shanlin; Kong, Hui; Xie, Weiping (Frontiers in Oncology, 2023)
Introduction Primary pulmonary lymphoepithelioma-like carcinoma (PPLELC) is a rare histological type of non-small cell lung cancer (NSCLC), which accounts for less than 1% of NSCLC. Currently, there is no well-recognized treatment guideline for PPLELC. Methods We identified PPLELC patients from the SEER dataset between year 2000 and 2015 (n=72) as well as from our medical center between year 2014 and 2020 (n=16). All diagnoses were confirmed by pathological testing, and clinicopathological characteristics of patients were retrieved and summarized. Survival analyses were conducted using Kaplan-Meier analysis and log-rank tests. Multivariate survival analysis was performed with Cox regression hazard model . Results The median age at diagnosis of the PPLELC cohort was 64 years old, with patients ranging 15-86 years old. The percentages of patients with TNM stage I, II, III, IV were 52.3%, 10.2%, 20.5%, and 17.0%, respectively. Among the 88 cases, lesion resection was performed in 69 cases (78.4%) , while 16 cases (18.1%) received beam radiation and 40 cases (45.5%) underwent chemotherapy. In SEER dataset of lung cancer, the percentage of PPLELC in the Asian race (0.528‰) was almost 10 times higher than that in the white (0.065‰) and black (0.056‰) races. Patients with TNM stage III-IV exhibited a worse prognosis than those with TNM stage I-II (P=0.008), with a 5-year cancer-specific survival (CSS) rate of 81.8% for TNM stage I-II and 56.2% for TNM stage III-IV. Specifically, N stage and M stage were the leading prognostic factors, not T stage and tumor size. Moreover, patients who underwent surgery had significant better outcomes than those who did not (P=0.014). Additional multivariate analysis indicated that TNM stage was an independent prognosis factor for CSS (HR, 3.31; 95% CI, 1.08-10.14). Conclusions PPLELC is a rare tumor with Asian susceptibility. Although the prognosis of PPLELC is better than other subtypes of NSCLC, it remains unsatisfactory for advanced stage disease. The current treatment options for PPLELC include surgical resection, chemotherapy, radiotherapy, and immune therapy. Among these options, patients with surgical resection have better survival rates in this study. However, Large-scale clinical research trials will be necessary to develop effective treatment guidelines for PPLELC.